Potential anti-inflammatory, antioxidant and antimicrobial activities of Sambucus australis. (1st January 2017) - Benevides Bahiense, Jhéssica; Marques, Franciane Martins; Figueira, Mariana Moreira; Vargas, Thais Souza; Kondratyuk, Tamara P.; Endringer, Denise Coutinho; Scherer, Rodrigo; Fronza, Marcio
Abstract: Context: Sambucus australis Cham. & Schltdl. (Adoxaceae) is used in Brazilian folk medicine to treat inflammatory disorders. Objective: To evaluate the in vitro anti-inflammatory, antioxidant and antimicrobial properties of S. australis . Materials and methods: The anti-inﬂammatory activity of ethanol extracts of the leaf and bark of S. australis (1–100 μg/mL) were studied in lipopolysaccharide/interferon γ stimulated murine macrophages RAW 264.7 cells (24 h incubation) by investigating the release of nitric oxide (NO) and tumour necrosis factor-alpha (TNF-α) and in the TNF-α-induced nuclear factor kappa (NF-κB) assay. Minimum inhibitory concentration (MIC) was determined by the microdilution test (24 h incubation). Antioxidant activity was determined by 2, 2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP) and the NO scavenging assays. Chemical composition was assessed by LC-MS/MS. Results: Antioxidant activities in the DPPH (IC50 43.5 and 66.2 μg/mL), FRAP (IC50 312.6 and 568.3 μg/mL) and NO radical scavenging assays (IC50 285.0 and 972.6 μg/mL) were observed in the leaf and bark ethanol extracts, respectively. Solely the leaf extract showed significant inhibition of NO and TNF-α production in RAW264.7 cells at concentrations of 2 and 100 μg/mL, respectively, and suppression of TNF-α inhibition of NF-κB by 12.8 and 20.4% at concentrations of 50 and 100 μg/mL, respectively. The extract also exhibited antibacterial activity against Salmonella typhimurium (MIC 250 μg/mL) and Klebsiella pneumoniae (MIC 250 μg/mL). LC-MS/MS revealed the presence of chlorogenic acid and rutin as major compounds. Discussion and conclusion: The results indicate that the ethanol leaf extract of S. australis exhibit prominent anti-inﬂammatory effects.